Peru : Selected Issues. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Selected Issues paper presents an overview of the financial deepening achievements and challenges in Peru. Although substantial progress has been made on various indicators of financial deepening, Peru lags regional and income peers in several respects. Peru's overall financial development index is modest, and its stage of financial depth does not fully align with domestic fundamentals. Private credit to GDP at about 40 percent of GDP is one of the lowest in the region, and below the expected level for a country at Peru's income and population. Studies also show that Peru has a negative gap in the depth and efficiency of financial institutions, which could reflect weak frameworks for obtaining or seizing collateral.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet